Development of Experimental Apparatus to Analyze Diesel Spray Characteristics - Razali, Mohd Azahari; Mohideen Batcha, Mohd Faizal; Madon, Rais Hanizam; Khalid, Amir; Mohmad Ja'at, Md Norrizam; Sapit, Azwan; Mohammed, Akmal Nizam; Mat Zaki, Muhammad Ameer; Samsubaha, Muhammad Fauzi (International Journal of Integrated Engineering, 2020)
Diesel engine performance and emission rely greatly on the diesel spray. A lot of researches conducted to study the diesel spray characteristics in a closed chamber. However, it cannot describe in detail about the phenomenon since the chamber condition such as pressure and size play a role in s pray characteristics. It would be beneficial to conduct an experiment in open chamber. Hence, this research would develop a new experiment apparatus and analyze the diesel spray characteristics in open chamber. In this research, common - rail injector tester is used to simulate the actual common - rail injection diesel engines. The injection pressure is varied from 100MPa to 180MPa. A high speed camera with 3,000 frames per second is used to capture the diesel spray formation using direct photography technique. From the result, spray development angle, and fully developed spray angle is studied. The results revealed early at the injection, the spray angle increased swiftly before slowly decreased as reaching fully developed spray phase. At the fully developed phase, spray angle proved to be decreased as the injection pressure increased.